2005
DOI: 10.1111/j.1601-5037.2005.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of self‐performed mechanical plaque control with triclosan containing dentifrices

Abstract: This systematic review indicates, based on studies >or=6 months of duration in adults with gingivitis, that the effectiveness of self-performed mechanical plaque control with a triclosan-containing dentifrice, had a significant albeit small positive effect on the reduction of plaque and gingivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 35 publications
8
52
1
Order By: Relevance
“…It has a broad spectrum of antibacterial activity and a significant anti-plaque effect, without staining the teeth. Systematic reviews of six-month clinical studies have concluded that formulations containing triclosan and copolymer significantly improve plaque control and periodontal health (15)(16)(17). Toothpastes containing triclosan and zinc citrate are also effective in improving plaque control and gingival health (18)(19)(20)(21).…”
Section: E978mentioning
confidence: 99%
“…It has a broad spectrum of antibacterial activity and a significant anti-plaque effect, without staining the teeth. Systematic reviews of six-month clinical studies have concluded that formulations containing triclosan and copolymer significantly improve plaque control and periodontal health (15)(16)(17). Toothpastes containing triclosan and zinc citrate are also effective in improving plaque control and gingival health (18)(19)(20)(21).…”
Section: E978mentioning
confidence: 99%
“…25% when no mouthwash was used. Gingival indices and BOP were significantly reduced after use of either mouthwash, whereas they increased significantly in the absence of a mouthwash régimen [36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…While some efficacy has been demonstrated for metal salts, a meta-analysis of stannous fluoride demonstrated significant heterogeneity in the findings of clinical studies (11) and most studies have shown zinc salts to be effective only when used in combination with other agents such as triclosan or chlorhexidine (10) . Triclosan has been shown to be effective against plaque and gingivitis in two systematic reviews (12)(13) ; however, a second systematic review with different inclusion/exclusion criteria failed to demonstrate 7 the same efficacy (11) . Furthermore, while triclosan is known to be safe for use in toothpaste formulations (14) , its use in a wide range of healthcare products have resulted in an accumulation of it and its breakdown products in the environment (15) .…”
Section: Introductionmentioning
confidence: 99%